Spatiotemporal Brain Maps of Delayed Word Repetition and Recognition - Dhond, Rupali P. (2005)
Whole-head magnetoencephalography (MEG) was used to spatiotemporally map the brain response underlying episodic retrieval of words studied a single time following a long delay (~40min.) Recognition following a long delay occurs as a strong, sustained, differential response, within bilateral, ventral and lateral prefrontal cortex, anterior temporal and medial parietal regions from ~500ms onward, as well as ventral occipitotemporal regions from ~700ms onward. In comparison with previous tasks using multiple repetitions at short delays, these effects were centered within the same areas (anteroventral temporal and ventral prefrontal), but were shifted to longer latencies (~500ms vs. ~200ms), were less left-lateralized, and appear more in anterolateral prefrontal regions and less in lateral temporal cortex. Furthermore, comparison of correctly classified words with misclassified, novel and repeated words, suggests that these frontotemporal-parietocingulate responses are sensitive to actual as well as perceived repetition. The results also suggest that lateral prefrontal regions may participate more in controlled, effortful retrieval while left ventral frontal and anterior temporal responses may support sustained lexicosemantic processing. Additionally, left ventromedial temporal sites may be relatively more involved in episodic retrieval, while lateral temporal sites may participate more in automatic priming.